Expressing Rules - Giacomo Turbanti (Rosenberg & Sellier, 2017)
The notion of conceptual normativity is grounded on the idea that our conceptual contents are established by the norms of the discursive social practices we engage in. This idea involves two major problems. First, where do the norms of discursive practices come from and how can the contents that they establish be objective? Second, what is the role of the vocabulary that we use to express such norms as explicit rules? This article draws the outline of an account that could possibly answer both questions. First, it explores the viability of a naturalism about conceptual normativity. Second, it defines the characters of a rational expressivist analysis of the language of the rules.